Faith as an asset in a community development project: The case of Madagascar - Rakotoarison, Zo R. (HTS teologiese studies, 2021)
Contributing to the emerging religion and development literature, this study sets out to analyse the role of faith in the context of a particular development approach, ‘Use Your Talents’ (UYT) at the Malagasy Lutheran Church in Madagascar. By analysing the views of lay Christian informants with regard to their involvement in the UYT project, the study asked what is the role of faith as an intangible asset in an asset-based community development project? The qualitative data were collected through participant observations and interviews conducted in four congregations across Madagascar in 2018. The results showed that church teachings and biblical stories created a normativity of good and desirable behaviour in the context of the asset-based community development project. Faith may constitute an asset when it promoted the individual’s capacity to achieve positive economic and social change.Contribution: This research broadened the understanding of religion in the context of asset-based community development projects. The results showed that the participants attributed their engagement in community development to their religious calling. The belief in the existence of a higher power not only seemed to influence individuals to act but also enabled them to feel empowered and have something to contribute. As a contribution to sociology of religion, this study showed that community development can be part of Christians’ and congregational holistic activities that depended on local knowledge and resources. Faith not only motivated individuals to engage in community development, but also it seemed to represent the essence of their engagement.